Legacy of kings - Herman, Eleanor, 1960- (Herman, Eleanor, 1960- Blood of gods and royals series, 2015)
Katerina, on a mission to kill the queen, falls in love with Alexander, Prince of Macedonia. Jacob will go to unthinkable lengths to win Katerina, even if it means having to compete with Hephaestion, a murderer sheltered by the prince. And far across the sea, Zofia, a Persian princess and Alexander's unmet betrothed, wants to alter her destiny by seeking the famed and deadly Spirit Eaters.